Product Quality Analysis Using FMEA and Fault Tree Analysis (FTA) Methods at Exotic UKM Intako - Nuzul Ardiansyah; Hana Catur Wahyuni (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2018)
Small and medium business of industrial bags and suitcases intako located in tanggulangin sidoarjo is a center producing varrious products such as bags, suitcases, and jacket in exotic store. Along with the increasing amount of production it must be coupled with the improvement of quality in order to be able to meet customer satisfaction. But in production activities often experience some obtacles one of them is product defect caused by human error and engine factor. This study uses the method Failure Mode and Effect Analysys (FMEA) to identify each stage of the process and the method Failure Tree Analisys (FTA) to find the root couse of failure . there are 6 potential failures ot the 4 production process of making bags with the highest RPN value such as sewing machine often having trouble with the value of RPN 504 and there are 12 basic event of FTA tree error depiction affecting product quality in exotic UKM intako.